How not to measure sustainable value (and how one might) - Kuosmanen, Timo; Kuosmanen, Natalia (Elsevier, 2009)
Sustainability is a complex multidimensional concept that entails economic, environmental, and social aspects. The sustainable value (SV) method developed by F. Figge and T. Hahn [Ecol. Econ. 48(2004) 173-187] is one of the most promising attempts to measure sustainability performance of firms. SV measures corporate contributions to sustainability by valuing resource use based on the opportunity cost, which must be estimated. This paper critically examines Figge and Hahn's estimator for opportunity cost, and shows that the proposed estimator rests on a number of strong, unrealistic assumptions. Evidence from Monte Carlo simulations conducted by authors shows that the proposed estimator performs very poorly even under ideal conditions. Having identified shortcomings in the SV method, we review some econometric approaches with a proven statistical foundation, which might be usefully applied in the present context.
Keywords: Ma; ekotehokkuus; ympäristötehokkuus; tehokkuusanalyysi; vaihtoehtoiskustannus; tuottavuus; kestävä kehitys; opportunity costs; sustainability; eco-efficiency; environmental performance; productive efficiency analysis